Too little sleep and an unhealthy diet could increase the risk of sustaining a new injury in adolescent elite athletes - von Rosen, P.; Frohm, A.; Kottorp, A.; Friden, C.; Heijne, A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Little is known about health variables and if these variables could increase the risk of injuries among adolescent elite athletes. The primary aim was to present overall data on self-perceived stress, nutrition intake, self-esteem, and sleep, as well as gender and age differences, on two occasions among adolescent elite athletes. A secondary aim was to study these health variables as potential risk factors on injury incidence. A questionnaire was e-mailed to 340 adolescent elite athletes on two occasions during a single school year: autumn semester and spring semester. The results show that during autumn semester, the recommended intake of fruits, vegetables, and fish was not met for 20%, 39%, and 43% of the adolescent elite athletes, respectively. The recommended amount of sleep during weekdays was not obtained by 19%. Multiple logistic regression showed that athletes sleeping more than 8 h of sleep during weekdays reduced the odds of injury with 61% (OR, 0.39; 95% CI, 0.16-0.99) and athletes reaching the recommended nutrition intake reduced the odds with 64% (OR, 0.36; 95% CI, 0.14-0.91). Our findings suggest that nutrition intake and sleep volume are of importance in understanding injury incidence.